Alleviation of salt-induced oxidative stress in rice seedlings by proline and/or glycinebetaine - N. Wutipraditkul; P. Wongwean; T. Buaboocha (Biologia Plantarum, 2015)
The effects of proline and/or glycine betaine (GB) application on growth, photosynthetic pigments, H2O2 content, and activities of antioxidant enzymes in rice (Oryza sativa L. cv. KDML105) under salt stress were investigated. The H2O2 content and the activities of superoxide dismutase (SOD), glutathione reductase (GR), and ascorbate peroxidase (APX) but not catalase (CAT) increased under salinity. Under 160 mM NaCl, the CAT activity was maintained on the pre-stress level in the presence of proline, whereas in the presence of GB, the GR activity increased more than without GB application. A co-application of 30 mM proline and 1 mM GB did not reduce the increase in H2O2 caused by the NaCl stress more than applying each of the osmoprotectants and no synergistic effect on the antioxidant enzymes was observed. However, the application of both the osmoprotectants was the most effective in alleviating degradation of photosynthetic pigments.